Gender Differences in Levodopa Pharmacokinetics in Levodopa-Naïve Patients With Parkinson’s Disease - Conti, Valeria; Izzo, Viviana; Russillo, Maria Claudia; Picillo, Marina; Amboni, Marianna; Scaglione, Cesa L. M.; Nicoletti, Alessandra; Cani, Ilaria; Cicero, Calogero E.; De Bellis, Emanuela; Charlier, Bruno; Giudice, Valentina; et al. (Frontiers in Medicine, 2022)
Background Levodopa (LD) is the most effective drug in the treatment of Parkinson’s disease (PD). Unfortunately, prolonged use of LD leads to complications, mainly motor/non-motor fluctuations (MNMF) and dyskinesias (DYS). Women seem more prone to develop such LD-related complications. Nonetheless, there is a paucity of prospective studies examining gender-related predictors of MNMF and DYS. Among several factors, which concur with a very complex scenario, changes in LD pharmacokinetics influence the drug’s effectiveness. The present study aimed to assess gender-related differences in LD pharmacokinetics in patients with PD at their first-ever intake of LD. Materials and Methods This is a multicentric study enrolling patients with PD, who were LD-naïve and received a single dose of LD/benserazide (100/25 mg) formulation. All participants gave their written informed consent, and the study was approved by the local Ethics Committees. To measure plasma LD concentrations and pharmacokinetic parameters (AUC, Cmax, Tmax, t1/2), fasting blood samples were collected before drug intake and then at 8-time points until 260 min. LD concentrations were measured by ultra-high-performance liquid chromatography coupled with mass spectrometry (UHPLC-MS). Multiple linear regression analyses were performed to identify the predictors of the parameters. Results Thirty-five patients (16 women and 19 men) were consecutively enrolled. Area under curve (AUC) and maximum plasma concentration (Cmax) were significantly higher in women than men (p = 0.0006 and p = 0.0014, respectively). No statistically significant difference was found regarding Tmax and t1/2. Multiple linear regression analyses revealed that female sex (β = 1.559116, 95% CI 0.8314479 2.286785; p < 0.0001) and body mass index (BMI) (β = −0.0970631, 95% CI −0.1733004 −0.0208258; p = 0.014) significantly predicted AUC. Only female sex significantly predicted Cmax (β = 1,582.499, 95% CI 731.581 2,433.417; p = 0.001). Moreover, only BMI significantly predicted t1/2 (β = 0.0756267, 95% CI 0.0143407 0.1369126; p = 0.017). Stratifying by gender, BMI was confirmed to significantly predict t1/2 in women (β = 0.1300486, 95% CI 0.0172322 0.242865; p = 0.027), but not in men. Conclusion This study provides novel insights on gender differences in LD pharmacokinetics, possibly contributing to the later development of motor complications and dyskinesia in PD.